The Influence of Institutional Support and Digital Self Efficacy on Teacher Motivation and Work Engagement at SMKN 1 Muaro Jambi - Maswana, Maswana; Kurniati, Erisa; Wulandari, Bunga Ayu (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study examines how institutional support and digital self-efficacy influence teachers’ motivation and work engagement, using SMKN 1 Muaro Jambi as the research site. Amid the rapid integration of digital technologies into education, it is essential to understand how both organizational factors and individual capabilities affect teaching dynamics. Adopting a quantitative approach, data were gathered from 53 teachers using structured questionnaires and analysed through the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The findings reveal that both institutional support and digital self-efficacy significantly enhance teacher motivation. Additionally, teacher motivation is found to be a strong predictor of work engagement, while institutional support also shows a direct positive relationship with engagement levels. Interestingly, digital self-efficacy does not directly influence engagement, suggesting its role is mediated through motivation. The originality of this research lies in its comprehensive model that integrates both institutional and personal resources to explain teacher engagement in a vocational education context during ongoing digital transformation. The insights from this study offer valuable input for educational stakeholders in developing strategies to strengthen teacher support systems and digital competencies.